Government Intervention Strategy in Agriculture Price Policy: A Case of Minimum Support Price in Nepal - Bhattarai, B.K.; GC, A. (Journal of Agriculture and Environment, 2020)
Price policies are used as important tools to enhance production, minimize the farmers’ risks and stabilize the consumer price. Different price policies are being implemented in many countries since long. This paper tries to analyze the different price policies – especial focused with minimum support price, implemented by Nepal and comparative assessment of their successes. The different literatures have been reviewed and policies of Nepalese government at different periods have been analyzed and compared with the relative performances to draw the conclusion. Implementation of Minimum support price and deficit payment schemes for different crops have been recommended, while establishment of separate commission for price and cost of agriculture commodities may ease the implementation of price policy.